Acetabular and Femoral Reconstruction in Total Hip Replacement for Adult Hip Dysplasia: A Technical Guide for Surgeons in Our Environment - Lawani, Olukemi; Okunola, Michael; Adeoye‑Sunday, Imoniche; Ayekoloye, Charles (Nigerian Journal of Orthopaedics and Trauma, 2019)
Hip dysplasia is abnormal development of the hip joint resulting in joint incongruity and characterised by a shallow acetabulum, inadequate femoral head coverage and femoral and acetabular version abnormalities. Childhood hip dysplasia is uncommon in this environment because of child swaddling practices. Adolescent onset forms are however not uncommon and present in adulthood more frequently than is recognized for total hip arthroplasty. Clinical and radiologic evaluation is key for diagnosis and surgical planning. The pathologic abnormalities on both sides of the hip joint present formidable challenges to total hip arthroplasty which remains the mainstay of treatment for end‑stage arthritis secondary to adult hip dysplasia. Posterior approach is preferred in our unit as it provides excellent acetabular exposure and enables assessment of sciatic nerve integrity when addressing leg‑length discrepancy common in this condition. Leg lengthening more than 3–4 cm should, however, be avoided with arthroplasty for this condition. We outline technical tips for successful total hip arthroplasty for this condition. This study aims to describe total hip arthroplasty in the setting of adult hip dysplasia. The objectives are to describe the pathologic changes in adult hip dysplasia, the evaluation of these patients and surgical technique.